THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION ACHIEVEMENT (A CASE TUDY) - Maria Noviana Hutabarat; Anshari Syafar (e-Journal of ELTS (English Language Teaching Society), 2021)
This study aims to find out the correlation between vocabulary mastery and reading comprehension. Research subjects were selected using cluster random sampling technique, that is taken from the class assigned (VIIIC). Before using the test items, they were tested their validity and reliability. The result of validity and reliability test showed that 15 out of 40 test items were not valid and reliable so they were not used to collect data. Data of vocabulary mastery were collected using essay test while data about reading comprehension were collected using multiple choice test. Data were analyzed using Pearson Product Moment coefficient correlation in the SPSS program version 20. The result of data analysis indicated that there is positive correlation between reading comprehension and vocabulary mastery (0.440) with significant level (α = 0.05). This result belongs to the category of moderate or medium correlation according to Best and Khan (0.40 to 0.59). Therefore, the hypothesis (Ha) of this research is failed to be rejected. It means that the greater the English vocabulary students have the better their reading comprehension do.